Antibody mimetic receptor proteins for label-free biosensors. Issue 3 (28th November 2014) - Raina, M.; Sharma, R.; Deacon, S. E.; Tiede, C.; Tomlinson, D.; Davies, A. G.; McPherson, M. J.; Wälti, C.
Abstract : Small synthetic antibody mimetic receptor proteins which offer high stability, specificity and affinity are presented as capture molecules in solid-state electro-chemical biosensors. Abstract : The development of high sensitivity biosensors, for example for clinical diagnostics, requires the identification of suitable receptor molecules which offer high stability, specificity and affinity, even when embedded into solid-state biosensor transducers. Here, we present an electrochemical biosensor employing small synthetic receptor proteins ( M w < 15 kDa) which emulate antibodies but with improved stability, sensitivity and molecular recognition properties, in particular when immobilized on a solid sensor surface. The synthetic receptor protein is a non-antibody-based protein scaffold with variable peptide regions inserted to provide the specific binding, and was designed to bind anti-myc tag antibody ( M w ∼ 150 kDa), as a proof-of-principle exemplar. Both the scaffold and the selected receptor protein were found to have high thermostability with melting temperatures of 101 °C and 85 °C, respectively. Furthermore, the secondary structures of the receptor protein were found to be very similar to that of the original native scaffold, despite the insertion of variable peptide loops that create the binding sites. A label-free electrochemical sensor was fabricated by functionalising a microfabricated gold electrode with the receptor protein. A change in the phase of the electrochemical impedance was observed when the biosensor was subjected to anti-myc tag antibodies at concentrations between 6.7 pM and 6.7 nM. These findings demonstrate that these non-antibody receptor proteins are excellent candidates for recognition molecules in label-free biosensors.